(untitled) (Journal of Telenursing (JOTING), 2022)
This study aims to analyze aspects of the Health Belief Model (HBM) with mothers’ compliance with ANC K4 visits during the COVID-19 pandemic in the working area of â€‹â€‹the Sikumana Health Center. The method used is quantitative with a cross-sectional design. The sampling technique uses simple random sampling. The results showed a significant relationship between maternal compliance with ANC K4 visits and the six aspects of HBM (perceived susceptibility, perceived seriousness, perceived benefit, perceived barrier, cues to action and self-efficacy). Data analysis using multiple logistic regression showed a simultaneous effect between perceived susceptibility (OR 8.315) and perceived benefit (OR 0.040) with maternal compliance with K4 antenatal visits; perceived susceptibility was the most dominant variable with p = 0.000, CI = 3.835 - 18,029. In conclusion, the HBM aspect that influences a mother’s adherence to ANC visits is Perceived susceptibility. Keywords: Health Belief Model, Compliance of Pregnant Women, K4 Antenatal Visits